Clinico-Epidemiological Profile and Treatment Outcomes of Testicular Germ Cell Tumors: A Retrospective Study from a Tertiary Cancer Center in Northeast India - Randhawa, Amritjot Singh; Dubey, Manas; Roy, Partha Sarathi; Hazarika, Munlima; Khanikar, Duncan (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Testicular Germ Cell Tumors (GCTs) are a common malignancy among young adults and are highly curable. However, in India, patients often present at advanced stages, leading to poorer outcomes compared to Western nations where earlier detection is more prevalent. Limited data exists on testicular GCTs from the Indian subcontinent. This retrospective study from the Tata Memorial Centre, Northeast India, explored the epidemiological, clinical, and treatment characteristics of GCTs in this region. Materials and Methods: This retrospective analysis was conducted on 72 patients diagnosed with testicular GCTs at Tata Memorial Centre - BBCI, Guwahati, from January 2018 to December 2022. Data collected included information related to the patients’ demographics, clinical presentation, staging, treatment, and outcomes. Results: Among 72 cases, 28 were seminomas and 44 were non-seminomas. Stage I was the most common presentation for seminomas (53.6%), while stage III was most prevalent in non-seminomas (77.2%). According to the International Germ Cell Cancer Collaborative Group (IGCCCG) classification, non-seminomas were categorized as good-risk (25%), intermediate-risk (35%), and poor-risk (40%). Seminomas exhibited a good-risk classification in 54% of cases and intermediate-risk in 46%. Conventional chemotherapy achieved radiologic complete response (CR) in 72% and partial response (PR) in 21% of seminoma patients. Among non-seminoma patients, CR and PR rates were 20% and 61%, respectively. The median recurrence-free survival (RFS) was 43 months. RFS was significantly better in seminomas compared to non-seminomas, stage I compared to stage III, and in the good-risk group compared to the high-risk group. Conclusion: This study highlights the significant challenge of advanced-stage presentation and high nodal burden in GCT patients from Northeast India. Non-seminomas demonstrated a predominantly partial response to conventional chemotherapy. Future research exploring alternative chemotherapy regimens to improve outcomes in this patient population is warranted.